Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The powers of the roots $\lambda$ of these polynomials $$p_n(x):=\sum_{k=1}^{n-1}\frac{n!}{(n-k)!}x^{k-1}$$ (compare with the $p_n$ here) sum to these values $$\sum_\lambda \lambda^k=-(-1)^k\frac{B_k}{k!} \textrm{for } k=1..n-2$$ The $B_k$ are the $k$th Bernoulli numbers $-\frac{1}{2}, \frac{1}{6}, 0, -\frac{1}{30}...$ Since $|\lambda|<1$ (fine to just assume) we have the geometric series $$\sum_{k=0}^\infty(\lambda x)^k=\frac{1}{1-\lambda x}$$ at least for $|x|\leq1$ but most of the $\lambda$ go to zero as $n$ increasesso the radius of convergence also may increase.

By summing over all $n-2$ roots $\lambda$ we get for the first $n-2$ terms of the left hand side. $$\sum_{k=1}^{n-2}(\lambda_1 x)^k+\sum_{k=1}^{n-2}(\lambda_2 x)^k+...=-\sum_{k=1}^{n-2}(-1)^kB_k\frac{x}{k!}^k$$ Which if you start at $k=0$ and go to $\infty$ converges to $-x/(1-\exp(-x))$ see here.

Question: Is $$-x/(1-\exp(-x))=\lim_{n\rightarrow \infty} \left (\sum_{p_n(\lambda)=0}\frac{1}{1-\lambda x}-n+1 \right)$$ at least for $|x|<1$? Here is a plot for $-x/(1-\exp(-x))$ (green) and $\sum_\lambda \frac{1}{1-\lambda x}-n+1$ (blue) for $n=16$

good fit for $|x|<1$

and the octave code to generate it

n = 16;

lambda = roots(factorial(n)./factorial(n - [n-1:-1:1]));

x = -10:1/10:20;

y = zeros(1,length(x));
for i = 1:length(x)
  y(i) = sum(1./(1-lambda*x(i)));

plot(x, y-n+1, 'b-', x, -x./(1-exp(-x)), 'g-')

axis([-10 +20 -20 +5])
share|cite|improve this question
up vote 5 down vote accepted

The desired limit formula holds for all real $x$, and even for all complex $x$ other than nonzero integer multiples of $2\pi i$.

The key is to write $\sum_{p_n(\lambda)=0} 1/(1-\lambda x)$ in terms of a logarithmic derivative.

We may assume $x\neq 0$. Define $$ q_n(x) = \frac{x^{n-1}}{n!} p(1/x) = \sum_{m=1}^{n-1} \frac{y^m}{m!} $$ (with $m=n-k$), so that $$ q_n(x) = x \prod_\lambda (1-\lambda x), $$ the product ranging over the $n-2$ zeros of $p_n$ (with multiplicity if necessary). Therefore $$ -x\frac{q'_n(x)}{q_n(x)} = -x \; \Bigl(\frac1x - \sum_\lambda \frac\lambda{1-\lambda x} \Bigr) = -1 + \sum_\lambda \frac{\lambda x}{1-\lambda x}. $$ Each summand $\frac{\lambda x}{1-\lambda x}$ can be written as $\frac1{1-\lambda x} - 1$, so the right-hand side is $$ \sum_\lambda \frac1{1-\lambda x} - n + 1. $$ On the left-hand side, $q'_n(x)$ is a partial sum of the power series for $e^x$, and $q_n(x)$ is a partial sum of the power series for $e^x-1$. These power series converge for all $x \in {\bf C}$. Therefore, as long as $e^x - 1 \neq 0$, $$ -x \frac{q'_n(x)}{q_n(x)} \rightarrow -x \frac{e^x}{e^x-1} = \frac{-x}{1-e^{-x}}, $$ and the proof is complete.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.